MENGULIK KETERLIBATAN DAN RELASI JEMAAT DALAM MODEL IBADAH ONLINE INTERAKTIF DI GEREJA BERNUANSA PENTAKOSTAL - Edrika, Vincentius (Sekolah Tinggi Teologi Imauel Pacet, 2025)
AbstractThe development of communication technology has driven changes in various aspects of life, including in church worship. GSJPDI Rajawali Anugerah uses interactive online worship that allows congregations from various locations, especially the Gospel Preaching Post (Pos PI), to stay connected with the central church. This research aims to examine more deeply the transformation of church worship in the digital era, especially online worship with an interactive approach and its relation to congregational involvement and relationships. Using a qualitative approach through interviews and observations, this study found that online worship that involves direct interaction between pastors and congregations, as well as between congregations from various PI Posts, can increase the spiritual attachment and solidarity of the church community. In addition, this worship model also contributes to deepening the understanding of God's Word and improving the spiritual discipline of the congregation. In conclusion, this interactive online worship is not only an alternative solution in worship but also plays a role in strengthening congregational involvement and relationships in the digital era.Keywords: “Congregational Involvement”, “Congregational Relations”, “Worship Transformation”, “Interactive Online Worship”